Fabrication of surface microstructures by mask electrolyte jet machining. (January 2020) - Wu, Ming; Liu, Jiangwen; He, Junfeng; Chen, Xiaolei; Guo, Zhongning
Abstract: This paper presents a novel electrochemical processing technique, mask electrolyte jet machining (MEJM), for the fabrication of surface microstructures. MEJM combines jet electrochemical micromachining (Jet-ECM) and through-mask electrochemical micromachining (TMEMM), combining the advantages of TMEMM, which is a high-throughput process, and of Jet-ECM, with its adjustable flow field. The effects of a mobile nozzle on electrolyte flow are investigated, and a new modeling approach for large translational movements is proposed. An analysis of the accuracy and reliability of the proposed method is presented. Microprotrusions and microdimples are produced to high precision and with excellent consistency of dimensional variation (maximum standard deviation 2.171 μ m). The results suggest the possibility of an affordable technique for batch fabrication of surface microstructures with high efficiency and precision. Graphical abstract: Image 1 Highlights: A novel electrochemical process for fabrication of micro surface structures. Assimilate the strong point of TMEMM and Jet-ECM, present a high-throughput process with adjustable flow field. The process shows potential especially considering large area complex geometries.